Predicting University Teachers’ Behavior Intentions Toward Digital Technologies: An Extension of the Unified Theory of Acceptance and Use of Technology Model (UTAUT) - Demuyakor, John; Doe, Vivian Adjeikaa; Tachie-Djan, Christian; Arshad Bhatti, Muhammad; Avenyo, Stevens Justice (Journal of Intelligent Communication, 2024)
Information and Communication Technologies over the past decades have enhanced University Teachers’ ability to provide effective and prompt teaching and learning. Therefore, this study explored University Teachers’ behaviour intentions toward the use of digital technologies for teaching and learning in higher educational institutions in Ghana. We grounded our study on the Unified Theory of Acceptance and Use of Technology (UTAUT) by testing the contributions of two key variables, the Cost of Internet Data and the Cost of Smart Phones to predict Behaviour Intentions (BI) of university teachers in three higher educational institutions towards the use of Digital Technologies (DTs) for online teaching and learning. We applied Partial Least Square Structural Equation Modelling for data analysis. Hypotheses testing on how the Cost of Internet Data and the Cost of Smartphones influence university teachers’ Behaviour Intentions (BI) toward the use of Digital Technologies (DTs) were supported. The findings of our study further showed that university teachers’ intentions to use DTs are influenced by determinants such as social influence, personal experience, and facilitating conditions. The study concludes that the polarity in the findings could help the university authorities to understand the factors to consider in selecting appropriate digital technologies for teaching and learning in universities. The findings from this study are a template for University teachers to get governments to change policies that affect the introduction of digital technologies in higher educational institutions.